2015
DOI: 10.1177/0363546515610552
|View full text |Cite
|
Sign up to set email alerts
|

Combined Subscapularis Tears in Massive Posterosuperior Rotator Cuff Tears

Abstract: The arthroscopic repair of massive tears results in substantial improvements in shoulder function, regardless of the presence of combined subscapularis tears. However, this study showed a trend toward a high failure rate for the repair of massive posterosuperior rotator cuff tears extending over half of the subscapularis tendon. Therefore, other treatment options should also be considered for this type of rotator cuff tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…, 8 However, their presence associated with supraspinatus tear are observed in more than 50% of arthroscopic rotator cuff repairs 9 10 Furukawa et al 14 observed subscapularis tear in 69% of their series, the majority consisting of partial- (35%) or full-thickness upper third tears (25%). MRI presents low sensitivity in the detection of these tears, especially in partial-thickness ones, which makes difficult the adequate diagnosis and treatment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…, 8 However, their presence associated with supraspinatus tear are observed in more than 50% of arthroscopic rotator cuff repairs 9 10 Furukawa et al 14 observed subscapularis tear in 69% of their series, the majority consisting of partial- (35%) or full-thickness upper third tears (25%). MRI presents low sensitivity in the detection of these tears, especially in partial-thickness ones, which makes difficult the adequate diagnosis and treatment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that 69% of large or massive tears were accompanied by subscapularis tears and many of these had concomitant complete rupture of the LHBT. 27) Park et al 28) showed that among patients who underwent arthroscopic repair for posterosuperior rotator cuff tears, patients with more than 50% of their subscapularis torn had a 43% retear rate, which was higher than in patients with less than 50% tears or no tears. Moreover, large subscapularis tears highlight the underlying decreases in both the cellularity of fibroblasts and the number of blood vessels that inhibit the healing capacity of a tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they initiate the regenerative responses following injury or degeneration. However, after the arthroscopic repair of rotator cuff, the re-tear rate has reported to be 25% to 91% [ 30 ]. That revealed the tendon-to-bone interface is unsuccessfully reintegrated.…”
Section: Resultsmentioning
confidence: 99%